A System Approach to Bahasa Indonesia - Damatius Wagiman Adisutrisno (Magister Scientiae, 2013)
In the last few decades, there have been a lot of undesirable changes in Bahasa Indonesia. The undesirable changes occur through coining new words, borrowing words from other languages, especially English, blending Bahasa Indonesia words and acronymizing words. Bahasa Indonesia users seem to exercise their complete freedom in using language. There is no control in coining words, borrowing words, blending words, and acronymizing words. The loss of control that leads to free will and right to use Bahasa Indonesia has caused Bahasa Indonesia chaos. If the free will and free right are not curbed, there will certainly be greater chaos. System approach teaches that Bahasa Indonesia serves the function as an official language and a national language. This function has to be maintained and preserved. If individuals belonging to Bangsa Indonesia continue to exercise their free will and free right in using Bahasa Indonesia, it can be predicted that Bahasa Indonesia will change from Indonesian Identity to British Identity